IMPLEMENTASI PENGGUNAAN POSITION POWER DAN PERSONAL POWER SERTA PENGARUHNYA TERHADAP KINERJA PEGAWAI UNIVERSITAS ISLAM NEGERI (UIN) MALANG - Achmad Sani Suprianto (ULUL ALBAB Jurnal Studi Islam, 2018)
The Study aims at, 1) finding out the simultaneuos influence of position power, and personnal power on the performance. 2) finding out the partially influence of position power, and personnal power on the performance. This is an explanatory research involving the employees of UIN Malang as the analysis unit. The studi used proportional random sampling method and to collect data from 36 respondent a questionnaire was used. The analysis technique used were multiple regression, partial regression, and determination. The result of study showed that :1) simultaneously the position power, and personnal power significantly influenced the performance, 2) partially the position power, personal power had also positive influence on the performance. Based on the finding, therefore it is suggested that the organization UIN Malang more attention to personnal po1oeer, is basically a dominant variable in influencing performance.The Study aims at, 1) finding out the simultaneuos influence of position power, and personnal power on the performance. 2) finding out the partially influence of position power, and personnal power on the performance. This is an explanatory research involving the employees of UIN Malang as the analysis unit. The studi used proportional random sampling method and to collect data from 36 respondent a questionnaire was used. The analysis technique used were multiple regression, partial regression, and determination. The result of study showed that :1) simultaneously the position power, and personnal power significantly influenced the performance, 2) partially the position power, personal power had also positive influence on the performance. Based on the finding, therefore it is suggested that the organization UIN Malang more attention to personnal po1oeer, is basically a dominant variable in influencing performance.